Melatonin ameliorates cuprizone‐induced reduction of hippocampal neurogenesis, brain‐derived neurotrophic factor, and phosphorylation of cyclic AMP response element‐binding protein in the mouse dentate gyrus - Kim, Woosuk (Brain Behav, 2019)
INTRODUCTION: The aim of this study was to investigate the effects of cuprizone on adult hippocampal neurogenesis in naïve mice. Additionally, we also studied how melatonin affects the neuronal degeneration induced by cuprizone. METHODS: Eight‐week‐old male C57BL/6J mice were randomly divided into three groups: (a) the control group, (b) the group treated with cuprizone only, and (c) the group treated with both cuprizone and melatonin. Cuprizone was administered with food at 0.2% ad libitum for 6 weeks. Melatonin was also administered with tap water at 6 g/L ad libitum for 6 weeks; the animals were then euthanized for immunohistochemistry with Ki67, doublecortin (DCX), glucose transporter 3 (GLUT3), and phosphorylation of cyclic adenosine monophosphate (AMP) response element binding (pCREB); double immunofluorescence of neuronal nuclei (NeuN) and myelin basic protein (MBP); and Western blot analysis of brain‐derived neurotrophic factor (BDNF) expression to reveal the effects of cuprizone and melatonin on cell damage and hippocampal neurogenesis. RESULTS: Administration of cuprizone significantly decreased the number of differentiating (DCX‐positive) neuroblasts and proliferating (Ki67‐positive) cells in the dentate gyrus. Moreover, cuprizone administration decreased glucose utilization (GLUT3‐positive cells) and cell transcription (pCREB‐positive cells and BDNF protein expression) in the dentate gyrus. Administration of melatonin ameliorated the cuprizone‐induced reduction of differentiating neuroblasts and proliferating cells, glucose utilization, and cell transcription. CONCLUSION: The results of the study suggest that cuprizone treatment disrupts hippocampal neurogenesis in the dentate gyrus by reducing BDNF levels and decreasing the phosphorylation of CREB. These effects were ameliorated by melatonin treatment.